Biomechanical effects of ball position on address position variables of elite golfers - Kim, S. E.; Koh, Y.-C.; Cho, J.-H.; Lee, S. Y.; Lee, H.-D.; Lee, S.-C. (Journal of Sports Science & Medicine, 2018)
The purpose of this study was to investigate address position variables in response to changes in ball position in golfers. Eleven male professional golfers were instructed to perform their golf swing. A three-dimensional motion analysis system, with eight infrared cameras and two force platforms, was used to capture the address positions. A golf ball has a diameter of 4.27 cm, and a radius of 2.14 cm. Even small movements of ball position in the mediolateral (M-L) and anteroposterior (A-P) directions significantly changed the address position. When the ball was moved to the left, the shoulder rotation and club-face aim rotated toward the left of the target, and the left vertical ground reaction force increased. When the ball was moved to the right, the opposite findings were observed. When the ball was moved closer, the trunk, hip, knee, ankle, and absolute arm angle extended; the lie angle of the golf club increased; and the center of pressure moved toward the posterior direction. These changes were reversed when the ball was moved further away. The M-L ball position critically changed the address positions of the upper extremities in the horizontal plane, and the A-P ball position critically changed the angles of whole body parts in the sagittal plane. Furthermore, club-head kinematics at impact such as club-face aim, club path, and angle of attack were significantly changed in the M-L ball position; and club-head speed and angle of attack were significantly changed in the A-P ball position. This in-depth understanding of the address position in association with the ball position could provide valuable data for swing coaches when finding a golfer`s optimal address positio